On Exact Non-Traveling Wave Solutions to the Generalized Nonlinear Kadomtsev–Petviashvili Equation in Plasma Physics and Fluid Mechanics - Shami A. M. Alsallami (Mathematics, 2025)
The Kadomtsev–Petviashvili (KP) equation serves as a powerful model for investigating various nonlinear wave phenomena in fluid dynamics, plasma physics, optics, and engineering. In this paper, by combining the method of separation of variables with the modified generalized exponential rational function method (mGERFM), abundant explicit exact non-traveling wave solutions for a (3+1)-dimensional generalized form of the equation are constructed. The proposed method utilizes a transformation approach to reduce the original equation to a simpler form. The derived solutions include several arbitrary functions, which enable the construction of a wide variety of exact solutions to the model. These solutions are expressed through diverse functional forms, such as exponential, trigonometric, and Jacobi elliptic functions. To the best of the author’s knowledge, these results are novel and have not been documented in prior studies. This study enhances understanding of wave dynamics in the equation and provides a practical method applicable to other related equations.